Steam cracker facilities in the United States: operations, emissions, and sociodemographic patterns of surrounding populations - Nicholaus P Johnson; Michelle L Bell; Nicholas Perez; Robert Dubrow; Nicole C Deziel (IOP Publishing, 2023)
Background: Production of shale gas in the United States (US) increased more than 10-fold from 2008 to 2021, yielding greater quantities of hydrocarbon feedstocks and incentivizing expansion of petrochemical facilities. Steam crackers (SCs) convert hydrocarbon feedstocks into ethylene and propylene (the building blocks of plastics), while releasing toxic chemicals and greenhouse gases (GHGs). Analyses of environmental health and justice impacts of SCs are limited. Methods: We described SC operations, locations, and emissions, and evaluated sociodemographic characteristics of populations residing near SCs to better understand potential public health hazards and inform future studies. We summarized and described industry-reported emissions from the US Environmental Protection Agency's Toxic Release Inventory and GHG Reporting Program. We compared population characteristics of US Census block groups ⩽5 km and >5 km from a steam cracker-containing facility (SCF) within the same county. Results: We identified 32 SCFs across five US states, with most in Texas and Louisiana. Toxic chemicals with the greatest reported cumulative air emissions in 1987-2019 were: ethylene, propylene, hydrochloric acid, benzene, n-hexane, 1,3-butadiene, ammonia, toluene, vinyl acetate, and methanol. Reported total annual GHG emissions were 4% higher in 2019 versus 2010, with total GHG emissions of >650 million metric tons (carbon dioxide equivalents) in 2010-2019. We found that 752 465 people live in census block groups ⩽5 km from an SCF, regardless of county. Compared to block groups >5 km away within the same county, block groups closer to SCFs had statistically significantly lower median incomes ($54 843 vs $67 866) and more vacant housing (15% vs 11%), and higher proportions of residents who were non-Hispanic Black (31% vs 19%) and unemployed (8% vs 6%). Conclusion: SCs emit substantial amounts of GHGs and toxic chemicals in locations with historically disadvantaged populations. Future research could further evaluate the accuracy of reported emissions, conduct monitoring in proximate communities, and assess population-level health impacts.